PENDEKATAN HERMENEUTIK NASR HAMID ABU ZAYD DALAM STUDI AL-QUR'AN: ANALISIS TERHADAP KONSEP TEKS DAN PRODUK BUDAYA - Iwan Setiawan; Abd Aziz (Al Burhan: Jurnal Kajian Ilmu dan Pengembangan Budaya Al-Qur'an, 2025)
This study examines Nasr Hamid Abu Zayd’s hermeneutical approach to the Quran, focusing on his concept of the Quran as a "cultural product" and its impact on modern exegesis. The method is qualitative content analysis of Abu Zayd’s works and related literature. Data were collected through library research and critically analyzed to identify intellectual patterns, controversies, and implications. Abu Zayd emphasized the historicity of the Quranic text and rejected static sacralization. Using literary-linguistic hermeneutics, he positioned the Quran as a cultural product requiring socio-historical contextualization. This approach led to the relativization of interpretation (e.g., polygamy in QS. An-Nisa: 3) and deconstruction of traditional Islamic sciences. However, it faced severe criticism from Salafi scholars for desacralizing the text. The conclusion is While Abu Zayd’s hermeneutics enables a dynamic Quranic reading, it risks undermining divine authenticity